EVALUATIONOFRENAL REPLACEMENT THERAPYQUALITY IN UKRAINE: TIME FOR ACTIONS - Kolesnyk, Mykola; Kozlyuk, Nadiya (Ukrainian Journal of Nephrology and Dialysis, 2015)
Background. Little is known about the status of renal replacement therapy (RRT) in the post-Soviet period of Ukraine. We therefore investigated the epidemiology and treatment outcomes of RRT in Ukrainian patients and put the results into an international perspective. Methods. Data from the Ukrainian National Renal Registry for patients on RRT between 1 January 2010 and 31 December 2012 were selected. We calculated the incidence and prevalence of RRT per million population (pmp) and the 3-, 12- and 24-month patient survival using the Kaplan— Meier method and Cox regression Results. There were 5985prevalent patients on RRT on 31 December 2012 (131,2 pmp). Mean age was 46,5 ± 13,8 years, 56% were men and 74% received haemodialysis (HD), while peritoneal dialysis and kidney transplantation both represented 13%. The most common cause of end-stage renal disease was glomerulonephritis (51%), while only 12% had diabetes. In 2012, 1129 patients started dialysis (incidence 24,8 pmp), with 80% on HD. Mean age was 48 ± 14 years, 58% were men and 20% had diabetes. Three, 12- and 24-month patient survival on dialysis was 95,1%, 86,0% and 76,4%, respectively. The transplant rate in 2012 was 2,1 pmp. Conclusions. The incidence and prevalence of RRT and the transplantation rate in Ukraine are among the lowest in Europe, suggesting that the need for RRT is not being met. Strategies to reduce the RRT deficit include the development and improvement of transplantation and home-based dialysis programs. Further evaluation of the quality of Ukrainian RRT care is needed.